Torsional wave dispersion relations in a pre-stressed bi-material compounded cylinder with an imperfect interface - Kepceler, Tamer (ELSEVIER SCIENCE INC, 2010)
This paper studies the influence of the imperfectness of the contact condition on the torsional wave propagation in the initially stressed (stretched) bi-material compounded circular cylinder. The investigation is carried out within the scope of the piecewise homogeneous body model with the use of the Three-dimensional Linearized Theory of Elastic Waves in Initially Stresses Bodies. The mathematical formulation of the corresponding eigen-value problem is formulated and the solution method for that is developed. The two cases considered are the hi-material compounded cylinder consists of the solid inner and surrounding hollow outer cylinders (Case 1); the hi-material compounded cylinder consists of the hollow inner and surrounding hollow outer cylinders (Case 2). The mechanical relations of the cylinders' materials are written through the Murnaghan potential. It is proven that the imperfectness of the contact condition does not influence the asymptotic-limit values of the wave propagation velocity. Moreover, the numerical results on the effects of the imperfectness of the boundary condition on the influence of the initial stresses on the wave propagation velocity are presented and discussed. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Torsional wave dispersion; Imperfect contact condition; Initial stress; Bi-material compounded cylinder; CIRCULAR COMPOSITE CYLINDERS; ELASTIC MEDIUM; PROPAGATION; RODS; SOLIDS; BODY; Engineering; Mathematics; Mechanics